Anthelmintic and antioxidant potential of banana bracts (Musa paradisiaca) extract in ruminants - Kakimori, Mônica Tiemi Aline; Debiage, Rafael Rostirolla; Gonçalves, Flávio Marcel Ferreira; Da Silva, Regildo Márcio Gonçalves [UNESP]; Yoshihara, Eidi; De Mello-Peixoto, Erika Cosendey Toledo (Editora da Universidade Federal Rural do Semi-Arido - EdUFERSA, 2019)
Pharmacological resistance to synthetic anthelmintic drugs is an important barrier to the control of animal parasites. Thus, this study aimed to evaluate the anthelmintic action of the hydroalcoholic extract of banana bracts (HEB) at 10%. Hatch test and larval migration inhibition test (LMI) were performed. Additionally, the total content of polyphenols, condensed tannins, and flavonoids was determined, along with the antioxidant activity of HEB. In relation to bovine species, HEB at a concentration of 2.5 mg mL-1 inhibited hatchability of nematode larvae by 88%. The LMI indicated 67.56% inhibition with 5 mg mL-1 HEB. However, in sheep, HEB did not show an influence in either tests. The HEB (10 mg mL-1) had 0.38 mg EAG g-1 of total polyphenols, 372.70 mg EAT g-1 tannins, 0.42 mg RE g-1 flavonoids, and presented antioxidant activity at 43.03% with IC50 corresponding to 0.2765 mg mL-1. Thus, HEB presents anthelmintic potential in vitro, for the parasitologic control in cattle, in addition to demonstrating antioxidant activity. These results are particularly important for agroecological, organic, and biodynamic systems of animal production, considering that the use of synthetic parasiticides is not allowed in these systems.
Keywords: Medicinal plants; Tannins; Worms